Pengaruh Kemitraan, Teknologi Informasi, Dukungan Eksternal, dan Inovasi Terbuka terhadap Keberlanjutan UMKM Kuliner (Studi Kasus: Bogor dan Depok) - Nur Widyanti, Oktarina; Siringoringo, Hotniar; Kuswanto, Adi (IPB University, 2025)
Culinary Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia’s economy, particularly in Bogor and Depok as buffer cities of Jakarta with highly competitive market dynamics, yet their business sustainability remains challenged by limited networking capacity, low digital literacy, and insufficient external support. This study aims to examine the influence of partnership, information technology utilization, external support, and open innovation on the sustainability of culinary MSMEs by developing an integrated model grounded in the Resource-Based View and Dynamic Capabilities theories to explain how internal and external factors shape business resilience. A quantitative explanatory approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0, based on survey data collected from 289 culinary MSME owners in Bogor and Depok through both online and offline questionnaires. The research instrument consisted of 21 indicators representing five main constructs. The findings reveal that partnership, information technology utilization, and external support have a positive and significant effect on business sustainability, with partnership emerging as the most dominant factor, while open innovation shows no significant influence due to the limited collaborative capacity and networking among local MSMEs. The model explains 64.1 percent of the variance in business sustainability, indicating strong predictive power. These results highlight the importance of strengthening strategic partnerships, accelerating digital adoption, and ensuring adaptive policy support as the foundation for long-term competitiveness and sustainability. Practically, this study offers strategic recommendations for MSME actors, local governments, and supporting institutions to enhance the resilience of the culinary sector in navigating market dynamics and digital transformation.